REFLECTIVE TEACHING IN THE ENGLISH TEACHING AND LEARNING PROCESS AT SMA NEGERI 5 KENDARI (A CASE STUDY) - Wa Ode Nurmaulid Sakti B (Universitas Negeri Padang, 2016)
The purpose of this study was to describe reflective teaching in the English Teaching and Learning process at SMA Negeri 5 Kendari. This study was a qualitative research with case study as the method of the study. The data were collected through questionnaire, interview, and observation while the data sources were taken from English teachers of SMA Negeri 5 Kendari that participate in this study. The result of the study indicated that the teacher was applying reflective teaching by using some strategies of reflective teaching. The teacher understood how they defined reflective teaching and recognized the importance of being reflective teacher. The teachers practiced reflective teaching by using some strategies of reflective teaching as suggested by Richards and Lockhart (1996). Lesson report, video recording, observation, action research, and students’ feedback were strategies of reflective teaching that practiced by the teacher in this study. Moreover, based on the analysis of questionnaire and interview, teachers stated the importance of being reflective were teacher learnt new things while teaching; teacher learnt from his/her own experiences as a learner and teacher; they developed their teaching skills and continuously improve their knowledge. Hence, teachers realized learning situation in the classroom while it was boring or not. However, in doing reflective teaching, they had some difficulties such as lack of time and heavy workloads. On the other hand, in doing peer observation, they got difficulties in encouraging their colleagues who lacked of readiness and focus of being reflective.